CCSP CSI Exam Certification Guide - Dubrawsky, Ido.; Grey, Paul. ([S.l.] : Cisco Press, 2003)
Prepare for the new CCSP CSI 642-541 exam with the only Cisco authorized CSI preparation guide available The only CCNP CSI guide developed in conjunction with Cisco Systems, providing the most accurate and current topical coverage Electronic testing engine on CD-ROM provides flexible assessment features and feedback on areas for further study Modular writing style and other features from Exam Certification Guide series provide superior learning, topic retention, and improved exam success This title is primarily intended for networking professionals pursuing the CCSP certification and preparing for the CSI 642-541 exam, one of five CCSP component exams. The materials, however, appeal to an even broader range of networking professionals seeking a better understanding of the Cisco SAFE Blueprint. The exam and course, known as Cisco SAFE Implementation (CSI), cover a broad range of networking security topics in the context of the overall Cisco SAFE Blueprint that guides network managers and engineers in determining which security solutions should be deployed throughout a given network. The SAFE strategy provides the foundation for migrating to secure, affordable, converged networks. It enables companies to cost-effectively deploy a modular, scalable security framework in stages and to deliver integrated network protection via high-level security products and services. CCSP CSI Exam Certification Guide (CCSP Self-Study) combines leading edge coverage of security concepts with all the proven learning and exam preparation features of the Exam Certification Guide series from Cisco Press. You'll find a CD-ROM testing engine with more than 200 questions, pre- and post-chapter quizzes, and a modular book and CD organization that breaks concepts into small, easy-to-absorb blocks of information. 158720089908212003.
Keywords: Computer networks; Security measures